2022
DOI: 10.1002/emp2.12722
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendicitis in the time of the COVID‐19 pandemic: A retrospective chart review

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Whilst higher complication rates and delays in the presentation of pediatric appendicitis were noted, a single-center retrospective analysis of pediatric appendicitis by Nassiri et al . 20 found no delay in presentation and no significant difference in the rates of complicated appendicitis. Another retrospective study conducted in Australia and New Zealand also concluded no difference in the presentation of symptoms and complication rates, with no delay in presentation to the emergency department 21 .…”
Section: Prevalence and Epidemiology Of Acute Appendicitis In Vulnera...mentioning
confidence: 65%
See 1 more Smart Citation
“…Whilst higher complication rates and delays in the presentation of pediatric appendicitis were noted, a single-center retrospective analysis of pediatric appendicitis by Nassiri et al . 20 found no delay in presentation and no significant difference in the rates of complicated appendicitis. Another retrospective study conducted in Australia and New Zealand also concluded no difference in the presentation of symptoms and complication rates, with no delay in presentation to the emergency department 21 .…”
Section: Prevalence and Epidemiology Of Acute Appendicitis In Vulnera...mentioning
confidence: 65%
“…Nassiri et al . 20 found a significant increase in the use of computed tomography scans during the pandemic in children with acute appendicitis, which raises concerns about unnecessary radiation exposure.…”
Section: General Diagnosis and Symptoms Of Pediatric Appendicitismentioning
confidence: 99%
“…This is true both for children with and without COVID-19, due to lockdowns and the potential for patient or family reluctance to attend hospital with presentation delayed. The impact of COVID-19 on disease severity at presentation is conflicting with the narrative differing between countries [24][25][26][27]. Higher rates of complicated appendicitis, possibly due to delays in presentation, have been reported in some populations, but this was not replicated universally.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles demonstrated that the COVID-19 pandemic had a serious impact on pediatric surgery services. [18,19,[31][32][33][34] The overall influence on pediatric surgery activity, as well as the impact on the specific type of surgical procedures, including elective and outpatient services, were analyzed. [35][36][37] In many hospitals, elective surgeries were temporarily suspended to ensure adequate hospital capacity to respond to the rapid spikes in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%